(untitled) (Journal of Universal Science Research, 2024)
This article describes the development software for a lighting control module based on Arduino Mega. At first main requirements for such software development are considered. These requirements include the following: lighting monitoring; determination of the normative level of illumination; deviation warning; lighting control. A client-server model was used. The client part is implemented in the form of a web interface, and the server part provides data storage and processing.